The Distributional Effects of Liberalizing the Exchange Rate In the Egyptian Economy During (1990-2018) - AL Agouza, Eman (The Arab Journal of Administration, 2023)
The Egyptian economy has been exposed to a number of internal and external shocks, which have negatively affected many of its macro variables, which pushed Egypt out of its economic crises to go to the International Monetary Fund to obtain a loan that would help it improve its economic and social conditions. There is no doubt that the loan resulted in Egypt's acceptance of a package of monetary and financial policies imposed on it by the International Monetary Fund, of which the trend towards liberalizing the exchange rate is one of its elements. The aim of the research is to study the distributional effects of liberalizing the exchange rate on the Egyptian economy, and the method was used to measure those effects by using a multivariate vector error correction model-VEC derived from a vector auto-regression model. It was concluded through the applied model that the Egyptian economy was negatively affected by the policy of liberalizing the exchange rate, in addition to the negative social effects that were generated within the framework of implementing that policy, which was reflected in the high level of poverty. Its adoption of this policy prepares the Egyptian economy for it and supports the social classes of the limited and middle-income groups.